High-flow nasal oxygen for suspension laryngoscopy: a multicenter open-label study. Issue 12 (December 2022) - Saad, Mary; Albi-Feldzer, Aline; Taouachi, Rabah; Wagner, Isabelle; Fischler, Marc; Squara, Pierre; Le Guen, Morgan
In this study, we aimed to assess the efficacy of high-flow nasal oxygen (HFNO) to maintain blood peripheral oxygen saturation (SpO2) in patients undergoing suspension laryngoscopy under general anesthesia. Adult patients were included in this bicenter study. After face-mask oxygenation, HFNO at a flow rate of 70 L min −1 and fraction of inspired oxygen 100% was initiated at loss of consciousness. At the end of HFNO, blood gas analysis was performed. Of the 29 included patients, five (17.2%; 95% confidence interval [CI]: 7.6–34.5) presented SpO2 <95% during the first 15 minutes of the procedure and eight patients (27.6%; 95% CI: 14.7–45.7) presented SpO2 <95% throughout the procedure. Six patients (20.7%; 95% CI: 9.8–38.4) required rescue jet ventilation. Median apnea time before SpO2 <95% was 13.5 (interquartile range [IQR]: 10–17.7) minutes. Arterial carbon dioxide tension at the end of the procedure or at the time of study discontinuation was 9.73 (IQR: 8.8–10.9) kPa and was higher than 8 kPa in 88.9% (95% CI: 71.9–96.1) of patients. HFNO was associated with a relatively high incidence of suboptimal oxygen saturation and hypercapnia during suspension laryngoscopy under general anesthesia and may not be considered the reference technique.